(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
This study evaluated the profitability and determined factors affecting the performance of oil palm processor in South West, Nigeria. Primary data were collected from two hundred and seventy-five (275) oil palm processors with the aid of structured validated questionnaire through a multi-stage sampling procedure. The data collected were analyzed using Seemingly Unrelated Regression Equation (SURE) and Budgetary Technique. The result revealed that the gross margin and profit of ₦498,534.6 and ₦357,367.9 respectively indicated that oil palm processing business was profitable. The Return on Investment (ROI) value of 1.63 showed that the processors had better performance. SURE, analysis showed experience and household size to be positively and significantly associated with profit while age, depreciation cost, labour cost and transportation cost showed inverse relationship with profit. On the other hand, education and experience showed positive and significant association with return on investment (ROI) while age, household size, depreciation, labour cost and transportation cost had a negative relationship with ROI. It is therefore, recommended that there should be policies which focus on education of processors that will promote performance in the oil palm processing business and extension training services that will enhance the processors experience in order to have a better performance.